Integrating Agroecology and One Health: A Path to Sustainable Food Systems and Improved Health - Tebourbi, Ons; Frija, Aymen; Alary, Veronique; Idoudi, Zied; Mannai, Amal; Rekik, Mourad (International Center for Agricultural Research in the Dry Areas, 2023)
Agroecology is increasingly gaining importance around the world, including in Tunisia: It is defined as a holistic approach to redesign food systems in the purpose of concurrently achieving ecological, economic, and social sustainability. In this paper, we argue that principles behind the agroecological transition of food systems can be fully aligned with the holistic approach of One Health, and we provide an early conceptualization for that. Bridging the approaches of One Health and Agroecology can be a significant promise for enhancing sustainability. This integration provides a means to effectively tackle the multifaceted and interconnected challenges confronting food systems, particularly those related to the health of the environment, animals, and humans. Adopting best agricultural practices and technologies can help achieve this. Some illustrative examples that highlight possible linkages of One Health to the agroecological approaches include embracing recycling and biodiversity to safeguard environmental health, reduce the reliance on chemical inputs, improve productivity and therefore reduce GHG emissions intensity, help combat resistance to antibiotics, antiparasitic, antivirals and antifungals, and enhance food safety. Additionally, prioritizing animal health and welfare within agroecological practices serves to protect both animal and human health, by reducing the risk of zoonotic diseases and further ensuring food safety. These examples have found their practical way in the Integrated Herd-Health Package (I2HP) which is now being co-developed and co-designed by the triangular consortium of ICARDA, National and Regional stakeholders and farmers’ groups. The herd structure and fitness component, the feed pillar, and the health component constitute the three key elements of this I2HP. The Integrated Herd-Health Package highlights how Agroecology and One health are interconnected and have the potential to significantly improve veterinary practices, public health outcomes and ecosystem resilience, making it a promising pathway toward improving the sustainability of food systems and advancing environmental, animal, and human health. This communication occurred during the 3rd Congress of the Ecole Nationale de Médecine Vétérinaire de Sidi Thabet (ENMV) "Le Véterinaire Face aux Changements" (ENMV/Tunis, Tunisia – 12-13 October 2023).